ADVANTAGES OF USING ARTIFICIAL INTELLIGENCE IN LITERATURE LESSONS (World Bulletin of Social Sciences, 2025)
This article explores the advantages of using artificial intelligence (AI) in literature lessons to enhance students’ learning experiences and teachers’ instructional practices. The study highlights how AI-powered tools can support deep text analysis, personalized learning, and creative engagement with literary works. Moreover, AI promotes multimodal approaches by integrating text, audio, and visual representations, which increase students’ motivation and understanding of complex artistic elements. The use of AI also enables efficient assessment, fosters collaboration, and develops critical digital literacy skills. By drawing on modern educational theories, the article argues that artificial intelligence can serve as an effective assistant in teaching literature, making lessons more interactive, accessible, and relevant to 21st-century learners